Outcomes of unconventional utilization of BI-RADS category 3 assessment at opportunistic screening - TÜRELİ, DERYA; KAYA, HANDAN (SAGE PUBLICATIONS LTD, 2016)
Background An important difficulty regarding the Breast Imaging Reporting and Data System (BI-RADS) category 3 assessment is the need for extensive diagnostic workup and an additional 6-month follow-up study. Purpose To evaluate the feasibility of the BI-RADS category 3 assessments at opportunistic screening. Material and Methods Mammography charts of 9062 screening patients in a major teaching hospital situated in an urban setting of a developing country were evaluated retrospectively (1997-2010). BI-RADS category 3 patients, called for a 6-month follow-up, which comprised a single-view spot or magnification mammogram. The length of follow-up period, compliance to periodic mammographic surveillance, cancer detection rate, and negative predictive values of category 3 assessments were calculated. Results Of the screened population, 9.2% were assigned BI-RADS category 3, and 31.2% of these cases were lost to follow-up. The mean follow-up period for 606 patients was 36.9 months. The negative predictive values for 6-month, 12-month, and final control studies were 90.9%, 87.5%, and 100%, respectively. Patient compliance for 6 months, 12 months, and any control evaluations beyond 12 months was low (50.0%, 29.8%, and 47.5%, respectively). Cancer detection rate was 0.8%. Conclusion Results of the study supports the feasibility of the BI-RADS category 3 assessments at opportunistic screening without any additional diagnostic workup. The practice of category 3 assessment following screening mammograms may be a more cost-effective method for developing countries with high recall rates and low resources in eliminating the maximum risk with minimum cost within the limits of available resources.
Keywords: Breast cancer; screening mammography; BI-RADS category 3; short-interval follow-up; cancer detection rate; PROBABLY BENIGN LESIONS; MAMMOGRAPHIC FOLLOW-UP; AMERICAN-COLLEGE; PREDICTIVE-VALUE; BREAST; MANAGEMENT; RECOMMENDATION; PATIENT